INTELEGEN PROSECUTOR'S ROLE IN INVESTIGATION OF ALLEGED CORRUPTION CASE - Wardhana, Metta Devyani Putri; Wirya Darma, I Made (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Law enforcement of criminal acts of corruption is carried out by the Prosecutor's Office. The issues raised in this paper are the role of the Bali High Court's intelligence in investigating alleged corruption cases and what obstacles the Bali High Court intelligence experienced in investigating alleged corruption cases. The research method that the author uses is empirical juridical. Juridically, answering the problem formulation is carried out by reviewing the applicable laws and regulations, while empirically, it is carried out by direct interviews with Mr. Joko Suryanto, S.H., M.H. as KASI Economy and Finance Intelligence field at KEJATI Bali. Data collection was carried out by collecting and studying case files and joint discussions. Based on the analysis of the data, the following research results were obtained: (1) The intelligence of the Attorney General's Office in handling corruption cases at the Bali High Court in general has a role, namely the first, in terms of investigating corruption cases by the intelligence of the Bali High Prosecutor's Office in order to obtain information and information material to proceed to the investigation process by the special criminal section. (2) The obstacles experienced by the Intelligence of the Prosecutor's Office in handling cases of criminal acts of corruption, namely, first in the case of calling the second witness, collecting evidence, and the fear of the party being questioned about the intervention of the relevant agency.